Analisis Marjin Pemasaran Kedelai di Kabupaten Grobogan - Bekti Wahyu Utami; Sapja Anantanyu (Caraka Tani: Journal of Sustainable Agriculture, 2007)
The aims of this study is identify soy marketing Marjin Analisys in sub-province Grobogan and active marketing institute of there, so we can know level of soy marketing margin. Result study shown marketing of soy in sub-province Grobogan entangle four componen, that is (1) farmer as producer; (2) Merchant Compiler; (3) whole Saler and (4) Consumer.